Ecological Epigenetics in Marine Metazoans - Hofmann, Gretchen E. (Frontiers in Marine Science, 2017)
In this horizon scan article, I review the emerging area of ecological epigenetics in marine animals with studies of DNA methylation as the primary focus. Epigenetic mechanisms such as DNA methylation have the capacity to create rapid changes in phenotypic plasticity. Epigenetic modifications of DNA are mechanisms that modify gene expression, and may do so in marine animals in an environmentally-induced manner. Thus, changes in the transcriptome that are driven by DNA methylation in response to environmental change may be one process by which marine animals can respond to anthropogenic, environmental change. From a technical standpoint, assays to quantify levels of DNA methylation, and next-generation sequencing approaches are opening up new avenues of exploration, such as simultaneously profiling the transcriptome and the methylome. A horizon scan for this topic suggests that the use of epigenomics and other methods to quantify DNA methylation will likely reveal important mechanisms of response to rapid environmental change in marine metazoans.